Oral health status of elderly residents in long-term care facilities and oral care experiences and educational needs of caregivers: A mixed methods study - Min-Joo Shin; Jae-Hun Koh; Eun-Jae Choi; Hye-Jin Kwon; Seon-Jip Kim; Hyo-Jin Lee; Hyewon Suh; Jijun Lim; Jung-Ah Lee; Hyun-Jae Cho (Journal of Korean Dental Association, 2026)
Purpose: This mixed-methods study aimed to investigate the oral health status of elderly residents in long-term care facilities and to explore caregivers' experiences and educational needs regarding oral care.Materials and Methods: Quantitative data were collected from 132 elderly residents in four facilities in Seoul through oral examinations and surveys. Differences in oral health indicators across long-term care grades were analyzed using Kruskal-Wallis and chi-square tests. Qualitative data were gathered through semi-structured indepth interviews as an exploratory qualitative inquiry.Results: The mean number of remaining teeth was 12.58±9.74. Approximately 54.7% of residents required partial or full assistance with toothbrushing. High prevalence rates were observed for masticatory discomfort (36.5%), food debris retention (50.4%), and dementia (73.9%). Qualitatively, caregivers identified oral care as their most burdensome task due to safety risks. Caregivers reported limited proficiency and insufficient access to oral hygiene aids appliance. They expressed a strong desire for practical, skill-based training, particularly regarding uncooperative residents, and showed positive perceptions toward VR-based simulation as a potential training modality.Conclusion: The oral health of institutionalized elderly is significantly poor, yet caregivers face challenges in providing adequate care. Although subjective oral health needs and the demand for assistance increased with care dependency, objective hygiene outcomes did not differ by grade, suggesting that oral care provision may not be sufficiently tailored to functional status. Systematic, skill-based education programs for caregivers and establishment of professional dental referral systems within long-term care settings are needed.